2013 IEEE Conference on Systems, Process &Amp; Control (ICSPC) 2013
DOI: 10.1109/spc.2013.6735092
|View full text |Cite
|
Sign up to set email alerts
|

The grading of agarwood oil quality using k-Nearest Neighbor (k-NN)

Abstract: This paper presents the application of k-Nearest Neighbor (k-NN) in grading the quality agarwood oil. Six agarwood oil samples obtained at Forest Research Institute Malaysia (FRIM) were extracted and their chemical compounds were examined by GC-MS. The work is followed by the grading system using the proposed k-NN. The study shows that there are 10 significant chemical compounds of agarwood oils. They are β-agarofuran, α-agarofuran, 10-epi--eudesmol, -eudesmol, longifolol, oxo-agarospirol, hexadecanol and eude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Based on the score of the accuracy and results of performance measure, it can be concluded that the k classifier model using number of neighbours of 1 to 8 provide the best results for classification of agarwood oil quality with 100% classification accuracy score. The computation efficiency and accuracy score obtained from this paper is higher when compared to the previous paper of classifying agarwood oil using k-NN method in [16].…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Based on the score of the accuracy and results of performance measure, it can be concluded that the k classifier model using number of neighbours of 1 to 8 provide the best results for classification of agarwood oil quality with 100% classification accuracy score. The computation efficiency and accuracy score obtained from this paper is higher when compared to the previous paper of classifying agarwood oil using k-NN method in [16].…”
mentioning
confidence: 67%
“…Some of the literatures are [13][14][15][16]. In [13], it carried out a research on predicting the yield of crops by using machine learning models.…”
Section: Machine Learning In Agriculture Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The best regression line of hidden neurons will be identified to discriminate the quality of Gaharu oil from high to low quality. Levenberg Marquadt (LM) algorithm was implemented for the trained dataset because it is the most commonly used optimization algorithm in many research studies [13], [38], [39]. The findings strongly showed that a best fit linear regression line with a value of R exactly 1 at hidden neurons number 2 which is the lowest compared to other neurons [40].…”
Section: Quality Grading System Of Essential Oilsmentioning
confidence: 99%
“…In case of utilizing code-aided synchronization, typically 8 outer iterations are performed (see Fig. 1) to achieve the desired communications performance as reported in Ali et al (2014). In such system, the demapper must deliver a throughput of 8-times 20 Msymbols/second.…”
Section: Introductionmentioning
confidence: 99%